De l’interprétation des liens entre vivants et morts dans l’espace habité maya Classique - Hemmamuthé Goudiaby (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
When faced with homogeneous funerary complexes, it is not always possible to discern the existence of different statuses among the dead. When they do exist, such differences often define how the living interacted with their forebears: how they were buried, how long they were remembered, what powers were bestowed upon them. As archaeologists, how do we identify such differences and, above all, what do they mean? Ancient Mayan funerary practices were closely associated with the habitats in which the dead were buried and they obeyed a spatial codification that still echoes among their descendants to this day. By associating archaeological observations and ethnographical data, it becomes possible to partially restore the place of the dead in a funerary hierarchy of greater subtlety than the sometimes omnipresent figure of the "ancestor" tends to suggest.